"To‐be‐forgotten" statements become less true: Memory processes involved in selection and forgetting lead to truthfulness changes of ambiguous sentences. Issue 3 (25th April 2017) - Santos, Ana Sofia; Ramos, Tânia; Garcia‐Marques, Leonel; Carneiro, Paula
Abstract : What happens when people try to forget something? What are the consequences of instructing people to intentionally forget a sentence? Recent studies employing the item‐method directed forgetting paradigm have shown that to‐be‐forgotten (TBF) items are, in a subsequent task, emotionally devaluated relative to to‐be‐remembered (TBR) items, an aftereffect of memory selection (Vivas, Marful, Panagiotidou & Bajo, 2016). As such, distractor devaluation by attentional selection generalizes to memory selection. In this study, we use the item‐method directed forgetting paradigm to test the effects of memory selection and inhibition on truth judgments of ambiguous sentences. We expected the relative standing of an item in the task (i.e., whether it was instructed to be remembered or forgotten) to affect the truthfulness value of that item, making TBF items less valid/truthful than TBR items. As predicted, ambiguous sentences associated with a "Forget" cue were subsequently judged as less true than sentences associated with a "Remember" cue, suggesting that instructions to intentionally forget a statement can produce changes in the validity/truthfulness of that statement. To our knowledge, this is the first study to show an influence of memory processes involved in selection and forgetting on the perceived truthfulness of sentences.